2012
DOI: 10.1016/j.jaci.2012.05.056
|View full text |Cite
|
Sign up to set email alerts
|

Response to infections in patients with asthma and atopic disease: An epiphenomenon or reflection of host susceptibility?

Abstract: Associations between respiratory infections and asthma inception and exacerbations are well established. Infant respiratory syncytial virus and rhinovirus infections are known to be associated with an increased risk of asthma development, and among children with prevalent asthma, 85% of asthma exacerbations are associated with viral infections. However, the exact nature of this relationship remains unclear. Is the increase in severity of infections an epiphenomenon, meaning respiratory infections just appear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
2
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 114 publications
(126 reference statements)
1
62
2
13
Order By: Relevance
“…The interaction between viral lower respiratory tract infections (LRTI) and atopic sensitization has been recognized as a major factor contributing to asthma development and exacerbation (86,87). Birth cohort studies provide strong evidence for a synergistic effect of viral LRTI and atopic sensitization on asthma inception particularly in predisposed children (56,88).…”
Section: Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between viral lower respiratory tract infections (LRTI) and atopic sensitization has been recognized as a major factor contributing to asthma development and exacerbation (86,87). Birth cohort studies provide strong evidence for a synergistic effect of viral LRTI and atopic sensitization on asthma inception particularly in predisposed children (56,88).…”
Section: Virusesmentioning
confidence: 99%
“…Also, allergic asthmatic individuals experience more severe and prolonged LRTI symptoms with RV infection compared to nonatopic healthy controls (93). Biological mechanisms including impaired innate or altered adaptive immune function, abnormal airway structure and function following prior infections, genetic influences and extrinsic factors, such as maternal smoking, air pollution and nutritional factors (vitamin D), may explain the altered immune response to viral infections in asthmatic/allergic patients (87). Recently, antibody titres to species-specific RV infection in children during asthma exacerbation showed that antibody response to RV-C is low even when the virus was detected, pointing to a divergent and possibly less efficacious immune response to this subtype compared to RV-A and B (94).…”
Section: Virusesmentioning
confidence: 99%
“…Previously, we suggested that atopy may be one factor in the delayed maturation of the immune system, leading to transient hypogammaglobulinemia at early ages [29]. Delayed postnatal maturation of the immune system, including a delayed transition from Th2 to Th1 bias, is a risk factor for respiratory infections [30].…”
Section: Discussionmentioning
confidence: 99%
“…2 During the H1N1 influenza epidemic in 2009, patients with BA developed pneumonia twice as often as people without allergies, 50% and 27% respectively, and the pneumonia was significantly more severe, requiring ICU admission in 33% and 19% of patients, respectively. 2 Infection with influenza in children with allergies during the 2009 epidemic was diagnosed much more frequently than in children without diagnosed allergies. 3 The risk of developing severe bronchial asthma is particularly high when the child is exposed to airborne allergens and a viral infection.…”
Section: The Susceptibility Of Patients With Allergies To Infectionmentioning
confidence: 99%